Associations of Karyotype and Age at Diagnosis with Physical Features and Comorbidities in Turner Syndrome: A Single-Site Experience - Vida B; Török O; Felszeghy E; Orosz M; Krasznai ZT; Tándor Z; Jakab A; Deli T (The Application of Clinical Genetics, 2025)
Beáta Vida,1 Olga Török,1 Enikő Felszeghy,2 Mónika Orosz,1 Zoárd Tibor Krasznai,1 Zoltán Tándor,1 Attila Jakab,1 Tamás Deli1 1Department of Obstetrics and Gynecology, Faculty of Medicine, University of Debrecen, Debrecen, H-4032, Hungary; 2Department of Pediatrics, Faculty of Medicine, University of Debrecen, Debrecen, H-4032, HungaryCorrespondence: Beáta Vida, Department of Obstetrics and Gynecology, Faculty of Medicine, University of Debrecen, Nagyerdei krt. 98, Debrecen, H-4032, Hungary, Tel +36204451350, Email vida.beata@med.unideb.huAim: Turner syndrome (TS) is one of the most common genetic diseases in females, with typical physical features and comorbidities. Karyotype-phenotype associations and clinical significance of childhood versus adolescent/adulthood diagnosis are conflicting.Purpose: Determining the role of certain TS karyotypes and early (< 12 years of age) vs late (≥ 12 years) diagnosis in TS-specific phenotype and comorbidity penetrance.Patients and Methods: Retrospective analysis of baseline characteristics and 45 TS-specific features and comorbidities of 75 TS patients were diagnosed between 2009 and 2019 and followed-up until 2023 in our tertiary care center.Results: Thirteen different karyotypes were detected: 45,X,inv(10), 45,X,inv(9)(15), 45,X, 46,X,i(Xq), 46,X,del(Xp), 46,XX,del(X)q21, 45,X/46,X,del(X), 45,X/46,X,+mar, 45,X/46,X,rX, 45,X/46,XX, 45,X/46,XY, 45,X/47,XXX, 46,X,i(Xq)/47,XX,i(Xq). The classic karyotype with 45X monosomy showed an increased risk for hypertrichosis (28.6% vs 7.5%, OR 4.93, 95% CI [1.23– 19.73]), pterygium colli (34% vs 12%, OR 3.65, 95% CI [1.13– 11.75]) and short stature (91% vs 75%, OR 3.56 [0.89– 14.17]. Mosaic karyotypes had a smaller risk of pterygium colli (OR 0.28 [0.073– 1.092]) and short stature (OR 0.29 [0.086– 1.026]. 45X/46XX mosaicism was associated with an increased risk of hypertension (33% vs 6%, OR 7.75 [1.39– 43.08]), and the presence of the iso (Xq) chromosome increased the risk of celiac disease (28% vs 3%, OR 13.2 [1.52– 114.52]). 44/75 (58.6%) of the cohort were diagnosed at < 12 years of age. In the < 12-year-old diagnosis group, facial dysmorphism and low hairline, (OR 3.30, [1.26– 8.65]), low-set ears (OR 2.51 [0.98– 6.46]), and breasts abnormalities (OR 4.71 [1.72– 12.83]), short stature (OR 4.09 [1.13– 14.82]) and GH therapy (OR 4.93 [1.31– 16.01]) occurred more frequently. If diagnosed < 12 years, patients had a decreased risk of hepatosplenomegaly (OR 0.10 [0.02– 0.50]) and hypertension (OR 0.097 [0.01– 0.85]).Conclusion: TS patients should be handled as a heterogenous group, as they seem to differ in the penetrance of phenotypical features of the disease and the risk of comorbidities depending on karyotype and age at diagnosis.Keywords: turner-syndrome, karyotype-phenotype association, comorbidities, mosaicism, incomplete penetrance, premature ovarian insufficiency